Cholesterol efflux and macrophage polarization in human adipose tissue - Králová, Anna; Bartušková, Hana; Kauerová, Soňa; Janoušek, Libor; Froněk, Jiří; Lesná, Ivana K; Poledne, Rudolf (Physiological research, 2022)
The pro-inflammatory status of adipose tissue (AT) has been found to be related to reverse cholesterol transport (RCT) from peritoneal macrophages. However, this finding was made in experimental models using induced peritonitis and isolated peritoneal macrophages of animals. This experimental relationship is in agreement with RCT changes in man in two extreme situations, sepsis or cardiovascular complications. Given the above, we sought to test RTC in relationship to macrophage polarization in the visceral AT (VAT) of living kidney donors (LKDs) and the effect of conditioned media obtained from their AT. The influence of ATCM on CE capacity was first assessed in an experiment where standard plasma was used as cholesterol acceptor from [14C] cholesterol labeled THP-1. Conditioned media as a product of LKDs' incubated AT showed no effect on CE. Likewise, we did not find any effect of individual plasma of LKDs on CE when individual plasma of LKDs were used as acceptors. On the other hand, we documented an effect of LKDs' adipose cell size on CE. Our results indicate that the pro-inflammatory status of human AT is not likely induced by disrupted RCT but might be influenced by the metabolic status of LKDs' adipose tissue.
Keywords: tuková tkáň; Cholesterol; makrofágy; Animals; Macrophages; Humans; lidé; Culture Media, Conditioned; cholesterol; zvířata; Adipose Tissue; kultivační média speciální